Trabalho e reconhecimento da soberania alimentar entre feirantes sergipanos - Xavier, Jair dos Santos (2024)
The agrarian market, sustained by control of land and the production of food products mainly for the external market, reflects the continuity of colonial exploitation. This production, financed by commodities in contemporary times, puts the production necessary for the dignified life of workers in second place, perpetuating their condition as exploited within the hegemonic system. Agribusiness is understood as an extension of Eurocentric domination that manifests itself today in neoliberal corporatism, deepening the economic dependence of the peripheries. This thesis analyzed the role of street vendors in promoting food sovereignty in Sergipe, focusing on their working conditions and the political influence on their autonomy. More specifically, we investigated the logic behind the collective action of these workers around their own class and their individual trajectories, in order to seek ways to understand the process of recognizing Food Sovereignty in the face of the hegemonic structure that we call here Agrobiopower. This thesis addresses the complex relationship between the agrarian market, food sovereignty, and workers in the agricultural and commercial food sector, with a specific focus on street vendors. It highlights how the street vendor is a crucial public space for articulating a possible struggle around both the workers’ cause and for a transformation in the food conditions of an entire population that has access to food through this same class. With this, we identify that the autonomy sought by street vendors is constantly suppressed, and the struggle for political transformation is crucial to breaking this cycle of precariousness. This thesis presents the concept of Agrobiopower, a form of biopower that controls not only the production and circulation of food, but also the possibilities of public discourse and action. Agrobiopower perpetuates economic dependence and limits the structural transformation necessary for food sovereignty. We thus emphasize the need to eliminate inequality in the recognition and redistribution of material and political resources, in order to build alternative models of democracy and the public sphere, capable of articulating the needs of workers and promoting significant changes, not only among market vendors linked to the fight for the cause of Food Sovereignty, but also among those who are grounded in the conventional labor process and are today direct victims of the logic imposed by Agrobiopower. In short, this research reveals the need for a new understanding of class in the agrarian context and proposes a critical and practical approach to transform the working and living conditions of market vendors, integrating social theory and political practice to confront the hegemonic structures of Agrobiopower, in order to promote a real democratic transformation based on a Food Sovereignty that brings together both casual and counter-hegemonic workers to maximize the effectiveness of the fight for food sovereignty, considering the needs of subordinate workers and promoting an effective and popular democratic transformation. In this way, this work allows us to understand, beyond the specific field, a set of changes in the world of informal and peasant work of the market vendor, in parallel with food activism in Sergipe and in Brazil.